Peran Orang Tua dalam Upaya Pemeliharaan Kesehatan Gigi terhadap Kejadian Karies Gigi pada Anak Usia 6-9 Tahun di SDN 169 Pekanbaru - Isnaniar; Norlita, Wiwik; Anggraeni, Vivi (As-Shiha: Jurnal Kesehatan, 2023)
Dental caries is a decayed area inside the tooth that occurs due to a process that gradually dissolves enamel (the hard outer tooth surface) and continues to develop to the inside of the tooth. One of the causes of dental caries is the role of parents in efforts to maintain dental health. Study results say that parental psychosocial factors that have been shown to negatively impact children's oral health include maternal depression, low coherence, pampering parenting and stressed parents. Parents' concern for children's dental health can be seen through their attitude and attention to children's dental health. The purpose of the study was to determine "the relationship between the role of parents in efforts to maintain dental health on the incidence of dental caries in children aged 6-9 years at SDN 169 Pekanbaru". The type of research used was cross sectional with accidental sampling techniques totaling 38 respondents. Data collection tools using questionnaires and data analysis used univariate and bivariate analysis. The results showed that parents who played a good role in children at SDN 169 Pekanbaru as many as 21 respondents (55.3%), and children who had caries as many as 22 respondents (57.9%). The test results using chi-square produced a significant value of 0.917. Significant test values of 0.917 > 0.05 show that there is no influence between the role of parents in efforts to maintain dental health on the incidence of dental caries in children aged 6-9 years at SDN 169 Pekanbaru.